Enhancing performance in professional water polo players: Dryland training, in-water training, and combined training - Saez de Villarreal, E.; Suarez-Arrones, L.; Requena, B.; Haff, G. G.; Ramos Veliz, R. (The Journal of Strength and Conditioning Research, 2015)
We compared the effects of 6 weeks of dryland, in-water-specific strength training and plyometric training combined with a water polo (WP) training program on 7 sport-specific performance parameters. Thirty professional players were randomly assigned to 3 experimental groups: combined training (CG), in-water-specific strength (WSG), and plyometrics (PG). The program included 3 weekly strength training sessions and 5 days of WP training per week for a total of 6 weeks during the preseason. The 10-m T-agility test, 20-m maximal sprint swim, maximal dynamic strength (1 repetition maximum [1RM], bench press [BP] and full squat [FS]), in-water boost, countermovement jump (CMJ) and throwing speed (ThS) were measured before and after the 6-week training period. There were no significant differences between the groups for any of the tested variables before the initiation of the 6-week training period. After 6 weeks of training, significant improvements (p = 0.001) were found in the PG group for the CMJ (6.1%) and in all groups for the in-water boost (4.4-5.1%) test. The 1RM BP (7.6-12.6%) and FS (11.5-14.6%) significantly (p = 0.05) increased in all groups. Additionally, ThS significantly increased in all groups (11.4-17.5%), whereas the agility test was significantly decreased (-7.3%) in only the CG group. Combined, in-water-specific strength and plyometric training produced medium to large effects on most WP-specific performance parameters. Therefore, we propose preseason WP training should include a combined training program that contains dryland and in-water-specific strength and plyometric training to optimize the WP preparation for competition.